2020
DOI: 10.1126/sciadv.abb5053
|View full text |Cite
|
Sign up to set email alerts
|

Infants tailor their attention to maximize learning

Abstract: Infants’ remarkable learning abilities allow them to rapidly acquire many complex skills. It has been suggested that infants achieve this learning by optimally allocating their attention to relevant stimuli in the environment, but the underlying mechanisms remain poorly understood. Here, we modeled infants’ looking behavior during a learning task through an ideal learner that quantified the informational structure of environmental stimuli. We show that saccadic latencies, looking time, and time spent engaged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 39 publications
7
93
0
Order By: Relevance
“…Accordingly, infants look longer at events (e.g., the appearance of an object from behind an occluder) when it can be characterized by medium–high predictability as opposed to very high or low predictability. This may serve to induce preference towards and longer observation of visual stimuli that maximize the chance of learning 25 as moderately predictable in contrast to highly predictable or unpredictable events can provide more new and relevant information for the infant. Another line of studies showed that infants are also able to track the degree of predictability of self-induced contingent reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, infants look longer at events (e.g., the appearance of an object from behind an occluder) when it can be characterized by medium–high predictability as opposed to very high or low predictability. This may serve to induce preference towards and longer observation of visual stimuli that maximize the chance of learning 25 as moderately predictable in contrast to highly predictable or unpredictable events can provide more new and relevant information for the infant. Another line of studies showed that infants are also able to track the degree of predictability of self-induced contingent reactions.…”
Section: Discussionmentioning
confidence: 99%
“…F. Baranes, Oudeyer, & Gottlieb, 2014). One recent infant study (Poli, Serino, Mars, & Hunnius, 2020) showed an association between LP and allocation of attention, but did not investigate this link in a multi-task, time-extended learning setting. Finally, our recent study presented direct evidence for adult humans' reliance on LP computation in a multitask setting with a distractor activity Ten, Kaushik, Oudeyer, & Gottlieb, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Infants' learning abilities are advanced from early in life 2,3 and possibly from birth 4,5 . However, whether infants are capable of meta-learning is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…If infants understood this structure, they could make use of it to change how they learned: By up-weighting evidence acquired early in the sequence and down-weighting evidence acquired later on, they could optimize their learning. 3 ) in which 16 sequences of cue-target pairs were shown. In each sequence, the cue consisted of a shape appearing in the middle of the screen.…”
Section: Introductionmentioning
confidence: 99%